Special Diets and Nutrient Intakes in Morbidly Obese US Adults in Comparison to the 2020–2025 Dietary Guidelines for Americans - Maximilian Andreas Storz; Frieda Stübing; Roman Huber (Nutrition Journal)
Abstract Background Morbid Obesity (MO), defined by a Body Mass Index (BMI) > 40 kg/m2, is the most severe form of obesity. The risk of suffering from any chronic medical condition is almost twice as high in MO as compared to overweight. Despite obesity being one of the most serious contemporary public health concerns, there is a paucity of nutrient intake data in adults with MO. Nutritional assessments in morbidly obese adults are often based on individuals seeking weight loss surgery rather than focusing on the general community. Methods Using National Health and Nutrition Examination Surveys data (NHANES, 2007–2016), we estimated nutrient intakes in the general US population with MO, thereby focusing on a comparative assessment to the Dietary Guidelines for Americans (DGA, 2020–2025). Nutrient intakes were assessed in morbidly obese US adults with a BMI > 40 kg/m2, regardless of their intention to seek weight loss treatment and regardless of reporting special diets. Sex- and age-specific nutrient intake assessments were performed, with the aim to identify population subgroups that may warrant particular attention from a public health perspective. Results The study sample comprised 1,708 participants with MO. This may be extrapolated to represent 14,047,276 US Americans. MO was more prevalent in females as compared to males (65.60% vs 34.40%) and the sample’s average age was 46.25 years, with a tendency towards a lower mean age in higher BMI groups. The alignment with the DGA was poor across both sexes, and particularly with regard to the nutrients of public health concern (fiber, calcium), saturated fatty acid intake and the intakes of several fat-soluble vitamins. Fiber intake was found to be particularly low in females with MO. Total energy intake was not associated with BMI in participants with MO. Morbidly obese individuals frequently reported special diets, with up to 28% of the examined population disclosing at least one special diet. Conclusions Using a descriptive epidemiological approach, we identified numerous sociodemographic and nutritional factors associated with MO. The poor alignment with US national dietary guidelines warrants special considerations and dedicated public health nutrition efforts to combat the increasing obesity-related burden.